CREATIVITY AND INNOVATIVENESS COMPETENCIES: DIFFERENCES AND SIMILARITIES (Scientific journal of the Fergana State University, 2026)
This article is devoted to analyzing the theoretical and practical foundations of the concepts of creativity and innovativeness. Creativity is interpreted as the ability to generate ideas and original thinking, whereas innovativeness refers to the potential to apply these ideas in practice and transform them into innovative products. The research results can serve as a basis for developing methodological recommendations for fostering creative and innovative competencies in education and professional activities.